‘Red Ruby’: an interactive web-based intervention for lifestyle modification on metabolic syndrome: a study protocol for a randomized controlled trial - Jahangiry, Leila (BioMed Central, 2014)
BACKGROUND: Although effectiveness of web-based interventions on lifestyle changes are recognized, the potential of such programs on metabolic syndrome has not been explored. We describe the protocol of a randomized controlled trial that aims to determine the feasibility, acceptability, usability, and effectiveness of interactive technology on lifestyle intervention in a population with metabolic syndrome. METHODS/DESIGN: This is a two-arm randomized controlled trial. The study includes 160 participants (n = 80 per arm) who will be recruited via online registration on the study website. The inclusion criteria are that they should have metabolic syndrome and have access to the Internet. All participants will receive information on dietary intake and physical activity through the study website. The intervention group will receive additional resources via the study website including interactive Healthy Heart Profile and calorie restricted diet tailored to the participants. The primary outcomes are feasibility, acceptability, usability, and the change in metabolic syndrome components. The secondary outcomes are comparing quality of life, physical activity and food intake among the study arms. The participants will be followed up to 6 months with data collection scheduled at baseline, 3 and 6 months. DISCUSSION: There is a need for developing and evaluating web-based interventions that target people with high risk for cardiovascular diseases. This study will therefore make an important contribution to this novel field of research and practice. TRIAL REGISTRATION: IRCT201111198132N1